The work of liberal health professionals in the COVID-19 pandemic context - Messias, Joao Carlos (2022)
As of March 2020, the COVID-19 pandemic made an important impact on work on a global scale. In the absence of a vaccine, the most adopted measures were social distance and preference for remote work. The present study sought to understand the meanings that eight health professionals attributed to their practices in this context. Meetings held with a dentist, a physician, an occupational therapist, a nurse, a psychologist, a physiotherapist, a speech therapist, and a nutritionist, were registered through comprehensive narratives. Three categories of results were found: 1) the meaning of work, 2) the option for liberal practice, and 3) the implications of the pandemic. It was possible to see how the effects of the pandemic were peculiarly experienced by each of the participants, in some cases making them reconsider the meaning of work in their lives.